A Survey of UAVs Detection: From Single UAV to Swarm - Montassar Abdenneji; Tijeni Delleji; Feten Slimeni; Rabah Attia (AI Society & STMIK Indonesia, 2026)
During the First World War, the world experienced the innovation of what is called drone, as a tool of espionage. Today we talk about drone swarm, where multiple drones work together to achieve a common goal or task. The use of this type of aircraft has undergone a great evolution and has become a source of problems for countries’ security, which incites researchers to look for solutions against drones. There are several detection methods such as acoustic, radar, visual, and thermal detection. Also, there is radio frequency (RF) detection based on the RF communication links of the drone system. All these methods of drone detection facilitate the mission of the fight against drones. This review presents a comprehensive study of single/multi-UAV (swarm) architectures and offers a critical analysis of detection methods, transitioning from a single to multi-drone context. The paper also highlights several potential research directions providing essential datasets related to the detection techniques. In addition to the theoretical literature review, this work paves the way toward the development of practical counter-UAV systems.